Design and performance of a centimetre-scale shrouded wind turbine for energy harvesting - Howey, D; Bansal, A; Holmes, A (IOP Publishing, 2011)
A miniature shrouded wind turbine aimed at energy harvesting for power delivery to wireless sensors in pipes and ducts is presented. The device has a rotor diameter of 2 cm, with an outer diameter of 3.2 cm, and generates electrical power by means of an axial-flux permanent magnet machine built into the shroud. Fabrication was accomplished using a combination of traditional machining, rapid prototyping, and flexible printed circuit board technology for the generator stator, with jewel bearings providing low friction and start up speed. Prototype devices can operate air speeds down to 3 ms⁻¹, and deliver between 80 μW and 2.5 mW of electrical power at air speeds in the range 3-7 ms⁻¹. Experimental turbine performance curves, obtained by wind tunnel testing and corrected for bearing losses using data obtained in separate vacuum run-down tests, are compared with the predictions of an elementary blade element momentum (BEM) model. The two show reasonable agreement at low tip speed ratios. However, in experiments where a maximum could be observed, the maximum power coefficient (~9%) is marginally lower than predicted from the BEM model and occurs at a lower than predicted tip speed ratio of around 0.6.